The Use of Three Steps Interview to Increase Students’ Self-Confidence at Speaking Skill - Nanang Sugianto (The Center for Language Development, Mataram State Islamic University., 2020)
This research aims to increase students’ self-confidence at speaking skill by using Three Step Interview at The Second Grade of MA Hadil Islah Bilebante. This research used Classroom Action Research (CAR) which was taken from Kemmis and McTaggarat’s design. This research was finished in one cycle that consisted of four phases, those were: planning, acting, observing, and reflection. The subject of this research was XI A class which consist 20 students. The method of this research was Three Step Interview which run into some steps; a) students made a group consists of 4 persons, b) teacher gave the topic to the students, c) students were in pairs, one was the interviewer and the other was the interviewee, d) students A interviewed students B and student C interviewed student B, e) students reserved roles and each shared with team member what was learned during the two interviews, f) the teacher gave the reward to the best group. The instruments used in this study were observation checklist and questionnaire. This action research was done in two cycles the standard students’ successful 80% or 80 from 20 students exceed criteria of success. The result of the study showed that students’ average score was 83.15 and 90% of students’ percentage or 18 from 20 students agree with application of Three Step Interview Technique in increase students’ self-confidence at speaking skill. Thus, the researcher concluded that this research was successful to increase students’ self-confidence at speaking skill.